Whataboutism in International Diplomacy: Shaping Third-Party Public Attitudes Toward U.S. Foreign Policy - Wilfred M. Chow; Dov H. Levin; Atsushi Tago (Journal of Conflict Resolution, 2026)
How does whataboutism influence the attitudes of third-party and allied audiences during international diplomatic exchanges? States openly accused of misconduct often employ whataboutism, deflecting criticism by highlighting the accuser’s own transgressions. Although policymakers frequently discuss whataboutism, research on its effects—especially on third-party publics—is limited. This study addresses the gap by examining via survey experiments a “hard case”: the impact of whataboutism targeting the U.S. on Japanese and the British publics, two steadfast U.S. allies. Our findings reveal that whataboutism significantly undermines support for the critic’s actions and diminishes the willingness of these populations to back sanctions led by the critic against states engaging in whataboutism. These results, the first empirical evidence of whataboutism’s effects on third-party allied publics, highlight whataboutism’s potency in shaping international public opinion, even among audiences from nations closely aligned with the critic country, potentially constraining U.S. foreign policy options.